HALAL VALUE CHAIN: A BIBLIOMETRIC ANALYSIS - Faza Muhlizoh A. Noer; Muhammad Ubaidillah Al Mustofa; Lissa Rosdiana Noer; Nafla Aqilah (Universitas Airlangga, 2025)
Introduction: Despite growing interest in halal research, there is a lack of complete understanding regarding the strategic contribution of the halal value chain to business performance and operations. Issues such as fragmented regulations and limited standardization beyond the food sector exacerbate this. This study aims to systematically analyze the evolution of halal value chain topics within academic discourse, identifying trends, evaluating the impact of research, recognizing key contributors, and suggesting directions for future research. Methods: This study adopts a bibliometric analysis methodology. The study analyzed 233 Scopus and 116 Web of Science-indexed research publications. The export data is then processed and analyzed using R-studio software to determine the bibliometric map of the halal value chain. Results: The findings demonstrate a significant increase in halal value chain research since 2011, with a primary concentration in Southeast Asia and a focus on micro, small, and medium-sized enterprises (MSMEs) and the halal food industry. Researchers have identified the gaps in non-food halal sectors, including cosmetics, pharmaceuticals, finance, and tourism. The analysis also highlights three strategic clusters—governance and certification, technological and operational integration, and market-oriented strategies—each contributing to economic, operational, and ethical outcomes. Conclusion and Suggestion: This study reveals that adopting a value chain perspective in halal supply chain management necessitates a comprehensive and integrated strategy. Future research should focus on empirical studies, sectoral diversification, and innovation in digital halal assurance to enhance the sustainability of the global halal ecosystem.